Enzyme immobilization method and application - LIU YAN; WU ZHONGLIU (2016)
The invention discloses a simple and convenient method for recombinase immobilization. According to the method, the characteristic that a histidine label of recombinant protein and metal ion affinity chromatography resin are combined specifically is utilized, and therefore recombinase is immobilized on the resin, and the immobilized recombinase is prepared. Immobilized carbonyl reductase is used for continuous production of chiral alcohol, and the space time yield is greatly increased. 本发明公开了种简便的方法用于重组酶的固定化，该方法利用重组蛋白的组氨酸标签与金属离子亲和层析树脂专性结合的特点，从而将酶固定于树脂上，制备固定化酶。以羰基还原酶固定化酶连续生产手性醇，大幅度提高了时空产率。